Respuesta :
Answer:
[tex]x=4\sqrt{3},\:x=-4\sqrt{3}[/tex] are the roots.
Step-by-step explanation:
[tex]x=4\sqrt{3},\:x=-4\sqrt{3}[/tex]
Considering the expression
[tex]x^2\:-\:48[/tex]
Solving
[tex]x^2-48=0[/tex]
[tex]x^2-48+48=0+48[/tex]
[tex]x^2=48[/tex]
[tex]\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}[/tex]
[tex]x=\sqrt{48},\:x=-\sqrt{48}[/tex]
Solving
[tex]x=\sqrt{48}[/tex]
= [tex]\sqrt{2^4\cdot \:3}[/tex]
[tex]\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b}[/tex]
= [tex]\sqrt{3}\sqrt{2^4}[/tex]
[tex]\mathrm{Apply\:radical\:rule}:\quad \sqrt[n]{a^m}=a^{\frac{m}{n}}[/tex]
[tex]\sqrt{2^4}=2^{\frac{4}{2}}=2^2[/tex]
[tex]=2^2\sqrt{3}[/tex]
[tex]=4\sqrt{3}[/tex]
So,
[tex]x=4\sqrt{3}[/tex]
Similarly,
[tex]x=-\sqrt{48}=-4\sqrt{3}[/tex]
Therefore, [tex]x=4\sqrt{3},\:x=-4\sqrt{3}[/tex] are the roots.
Keywords: roots, expression
Learn more about roots from brainly.com/question/3731376
#learnwithBrainly
Answer:
The solutions are [tex]x=4\sqrt{3}[/tex] an [tex]x=-4\sqrt{3}[/tex]
Step-by-step explanation:
We want to find the root of the quadratic function [tex]f(x)=x^2-48[/tex]
To find the roots of this function, we set f(x)=0
This implies that:
[tex]x^2-48=0[/tex]
This implies that:
[tex]x^2=48[/tex]
Take square root to get;
[tex]x=\pm \sqrt{48}[/tex]
[tex]x=\pm4\sqrt{3}[/tex]
Therefore the solutions are [tex]x=4\sqrt{3}[/tex] an [tex]x=-4\sqrt{3}[/tex]